2018
DOI: 10.1371/journal.pone.0192104
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent interactive effects of non-lethal predation on larvae impact adult longevity and body composition

Abstract: Predation impacts development, behavior and morphology of prey species thereby shaping their abundances, distribution and community structure. Non-lethal threat of predation, specifically, can have a strong influence on prey lifehistory characteristics. While investigations often focus on the impact of predation threat on prey in isolation, tests of its interactive effects with food availability and resource competition on prey survival and fitness can improve understanding of costs, benefits and trade-offs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 105 publications
0
39
2
Order By: Relevance
“…aegypti females exposed to predator risk during the larval stage [23]. Similarly, Chandrasegaran et al [35] found https://doi.org/10.1371/journal.pone.0241070.g004…”
Section: Discussionmentioning
confidence: 91%
“…aegypti females exposed to predator risk during the larval stage [23]. Similarly, Chandrasegaran et al [35] found https://doi.org/10.1371/journal.pone.0241070.g004…”
Section: Discussionmentioning
confidence: 91%
“…Although female larvae may not change behavior as strongly as do males in response to predator cues (Wormington & Juliano, ), females still may face significant life‐history costs from any reduction in foraging due to their higher demand for resources to produce greater adult body size. Other studies on trait‐mediated effects of predation or predation cues on mosquitoes have found retarded larval growth and development, reduced adult size, shortened adult longevity, and reduced teneral reserves of lipid, protein, and carbohydrate ( Culex pipiens : Beketov & Liess, ; Aedes notoscriptus : van Uitregt et al, ; Aedes aegypti : Bellamy & Alto, ; Chandrasegaran et al, ), and females are usually more strongly affected than males due to greater reproductive costs (Chandrasegaran et al, ; Wormington & Juliano, ). These nonlethal effects of predators are more likely to be important and detectable when food availability to larvae is limited.…”
Section: Discussionmentioning
confidence: 99%
“…We found no effects of predator cues on males, but significant life-history costs of predator cue exposure for females (decrease in survivorship, significantly faster emergence times when given higher resource levels, significantly reduced adult longevity when given lower resource levels). Male A. triseriatus exhibit a more extreme shift in behavior in response to predator cues than do females-particularly when they are well-fed-increasing their resting behavior at the surface which reduces their predation risk (Wormington & Juliano, 2014 Chandrasegaran et al, 2018), and females are usually more strongly affected than males due to greater reproductive costs (Chandrasegaran et al, 2018;Wormington & Juliano, 2014). These nonlethal effects of predators are more likely to be important and detectable when food availability to larvae is limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations